Integrating Islamic principles into human resource management: Advancing organizational success through Islamic education and ethical practices - Auwal Gano, Abdulmalik; Abdullahi, Nazifi; Lawan Adam, Zahraddin; Setyawan, Cahya Edi (Tadibia Islamika: Journal of Holistic Islamic Education, 2024)
The effectiveness of organizational performance is deeply influenced by the quality of human resource management (HRM). When implemented effectively, HRM serves as a strategic tool that enhances organizational success. For Muslims, Islamic principles are integral to every aspect of life, including HRM. However, the implementation of Islamic HRM practices faces a significant challenge: the lack of sufficient Islamic education in this field. This research addresses this gap by exploring strategies for integrating Islamic principles into HRM practices, emphasizing the role of Islamic education in equipping HR managers with the necessary knowledge and ethical framework. The study examines key HRM functions, including recruitment, selection, orientation, performance evaluation, training and development, compensation and benefits, and career development, through the lens of Islamic teachings. Using an exploratory qualitative approach, the research reviews existing literature from academic journals, books, and articles on Islamic management principles and HRM practices. The findings reveal that incorporating sharia principles into HRM functions not only leads to mutually beneficial outcomes for employers and employees but also aligns professional practices with spiritual goals, securing blessings and rewards from Allah. The study concludes that organizations and their workforce can achieve both worldly success and spiritual fulfillment when HRM practices are aligned with Islamic principles, underscoring the importance of Islamic education in realizing this potential.